Effects of quinolines on SW480 colorectal cancer cells: gap junction dependent and independent pathways - Bigelow, Kristina Marie (Kansas State University, 2014)
Colorectal cancer is one of the most common cancers in the United States with an early detection rate of only 39%. Colorectal cancer cells along with other cancer cells exhibit many deficiencies in cell-to-cell communication, particularly gap junctional intercellular communication (GJIC). GJIC has been reported to diminish as cancer cells progress. Gap junctions are intercellular channels composed of connexin proteins, which mediate the direct passage of small molecules from one cell to the next. They are involved in the regulation of the cell cycle, cell differentiation, and cell signaling. Since the regulation of gap junctions is lost in colorectal cancer cells, the goal of this study is to determine the effect of GJIC restoration in colorectal cancer cells. Overexpression of connexin 43 (Cx43) in SW480 colorectal cancer cells causes a 6-fold increase of gap junction activity compared to control un-transfected cells. This suggests that overexpressing Cx43 can restore GJIC. Furthermore, small molecule directly targeting gap junction channel was used to increase GJIC. Gap junction enhancers, PQs, at 200 nM showed a 4-fold increase of gap junction activity in SW480 cells. Using Western blot analysis, Cx43 isoform expression was seen to shift from P0 to P1 and P2 isoforms after treatment with PQ1 200 nM for 1 hour. Overall, the results show that overexpression of connexin and small molecules such as gap junction enhancers, PQs, can directly increase gap junction activity. The findings provide an important implication in which restoration of gap junction activity can be targeted for drug development.
Keywords: Cancer; Gap Junctions; Substituted Quinoline; Molecular Biology (0307)